Enantioselective Synthesis of Chiral Carboxylic Acids from Alkynes and Formic Acid by Nickel‐Catalyzed Cascade Reactions: Facile Synthesis of Profens. Issue 1 (18th November 2021) - Yang, Peng; Sun, Yaxin; Fu, Kaiyue; Zhang, Li; Yang, Guang; Yue, Jieyu; Ma, Yu; Zhou, Jianrong Steve; Tang, Bo
Abstract: We report a stereoselective conversion of terminal alkynes to α‐chiral carboxylic acids using a nickel‐catalyzed domino hydrocarboxylation‐transfer hydrogenation reaction. A simple nickel/BenzP* catalyst displayed high activity in both steps of regioselective hydrocarboxylation of alkynes and subsequent asymmetric transfer hydrogenation. The reaction was successfully applied in enantioselective preparation of three nonsteroidal anti‐inflammatory profens (>90 % ees) and the chiral fragment of AZD2716. Abstract : A simple nickel catalyst converts terminal alkynes and formic acid to α‐chiral carboxylic acids in high enantioselectivity. The reaction proceeds via the hydrocarboxylation of alkynes and enantioselective transfer hydrogenation of acrylic acids.